ANALYSIS OF WAYS TO INCREASE COMPETITIVENESS UKRAINIAN METALLURGICAL ENTERPRISES ON THE EXAMPLE OF PJSC "ARCELORMITTAL KRYVIY RIH". PART 2. STEELMAKING PROCESS - CHUPRYNOV, YEVHEN; KORENKO, MARYNA; KASSIM, DARIA; REKOV, YURIY; MALII, KHRYSTYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article investigates the influence of various factors on the temperature regime of the oxygen-converter process in the conditions of PJSC "ArcelorMittal Kryvyi Rih". It is shown that the metal temperature is a critically important parameter. In order to clarify the causes of temperature fluctuations and optimize the technological process, a statistical analysis of melt passports was conducted. The dependence of the metal temperature on the first tap on the temperature and mass of the poured liquid iron was established, which allowed developing an accurate model for predicting the temperature regime. A correlation was found between the metal temperature during blowing and the manganese content in the iron. The influence of the charge components on the temperature regime was analyzed in detail. It was confirmed that scrap, due to its larger surface area and slag content, causes a significant decrease in temperature. The influence of "goat" scrap, which, unlike scrap, does not contribute to cooling, as well as limestone (CaCO3), which is used to compensate for excess heat, was investigated. Optimization of limestone utilization is an important task due to its relatively low reactivity. A set of corrective measures is proposed to increase the efficiency of oxygen-based furnace production. It is recommended to adapt the technological process to different types of scrap, optimize the use of limestone and coke, apply flame cutting for " goat" scrap, carry out operational control of the reaction zone temperature, and implement a mathematical model of process control. A method for calculating the temperature of the radiating surface of the reaction zone based on the heat flux transferred to the cooling water, taking into account the oxygen consumption and the position of the lance, is described. The implementation of the proposed solutions will contribute to increasing the flexibility of steelmaking technology in conditions of instability of charge materials.